Lecturer Mentoring on SINTA, Garuda, and Google Scholar at STIKES Abdurrahman and ITB Bina Sriwijaya Palembang - Muhammad Ridho Ardiansyah; Mahmud; Indah Rahma Sari; Hendriansyah; Martini; Nabila Kintan Oktadinna (Indonesian Journal of Community Engagement, 2026)
Mentoring activities in managing SINTA, Garuda, and Google Scholar accounts represent a strategic effort to improve the quality of lecturer publication governance and the performance of higher education institutions. This study aims to describe the process and outcomes of mentoring activities related to the management of SINTA, Garuda, and Google Scholar accounts for lecturers at STIKES Abdurahman Palembang and Institut Bina Sriwijaya Palembang. The study employed a qualitative approach with a descriptive design. Data were collected through observation, documentation, and field notes during the implementation of the mentoring activities. The mentoring was conducted through material presentations, hands-on practice, and individual assistance, focusing on profile updates, publication synchronization, metadata improvement, and the creation of global researcher identifiers such as ORCID and Web of Science. The results indicate a significant improvement in institutional publication performance, particularly at Institut Bina Sriwijaya Palembang, as evidenced by an increase in the number of verified authors, SINTA Overall Score, SINTA 3-Year Score, and SINTA productivity. Meanwhile, at STIKES Abdurahman Palembang, the mentoring activities contributed to improving the accuracy and validity of lecturer publication data through cross-platform account synchronization. Overall, these mentoring activities proved effective in enhancing the quality of lecturer publication management, increasing participant engagement, and supporting sustainable improvements in academic performance and institutional visibility.